2021
DOI: 10.1126/sciadv.abf7207
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal exosome–functionalized scaffolds induce innate and adaptive immunomodulatory responses toward tissue repair

Abstract: Designing scaffolds capable of inducing and guiding appropriate immune responses holds promise for tissue repair/regeneration. Biofunctional scaffolds were here prepared by immobilizing mesenchymal stromal exosomes onto fibrous polyester materials and allowed cell-mediated delivery of membrane-bound vesicles. Quantitative cell-level analyses revealed that immune cells dominated the uptake of exosomes from scaffolds in vivo, with materials and exosomes acting as the recruiter and trainer for immune cells, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 42 publications
4
60
0
Order By: Relevance
“…The development of the active composition of CDN-laden scaffolds that appropriately interact with the immune system is facing a huge challenge. Studies have found that immune cells can absorb exosomes from the scaffold with more priority, which means that the body's immune response is important in tissue response [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of the active composition of CDN-laden scaffolds that appropriately interact with the immune system is facing a huge challenge. Studies have found that immune cells can absorb exosomes from the scaffold with more priority, which means that the body's immune response is important in tissue response [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, known as membrane-enclosed extracellular vesicles (EVs) that carry proteins and nucleic acids, might represent another type of delivery system of bioactive molecules [ 180 ]. Su et al developed biofunctional scaffolds by fixing mesenchymal stromal exosomes (Exo) to electrospun randomly oriented fibrous polyester materials (PEF) [ 156 ]. The fabricated scaffolds were examined in skin injury models of sham mice to understand the immunomodulatory effects of mesenchymal stromal exosomes (Exo) in vivo [ 156 ].…”
Section: Scaffold Immunoengineering Strategies For Tendon Te Applicationsmentioning
confidence: 99%
“…Recently, scaffolds and exosomes from mice BM-MSCs were developed as a combinatorial cell-free system to initiate synergistic tissue immunotrophic effects. Indeed, exosome-laden scaffolds (fibrous polyester materials) proactively facilitated tissue repair in mice skin injury models by favoring M2/T H 2/Treg responses ( Su et al, 2021 ). Together, all these findings indicate that combined HA and MSCs may constitute an effective strategy in regenerative medicine.…”
Section: Therapeutic Applications Of Mscsmentioning
confidence: 99%